THE EFFECT OF PLASTIC COVERS WITH DIFFERENT COLOR ON THE TYPE AND ABUNDANCE OF EPIPELIC DIATOMS IN THE NATURAL LOVERS INTERTIDAL AREA (PAB) CITY OF DUMAI - Nisa, Chairun; Siregar, Sofyan Husein; Nasution, Syafruddin (Asian Journal of Aquatic Sciences, 2023)
The purpose of this study was to determine the effect of the plastic cover with different colors on the type and abundance of epipelic diatoms. This research was conducted in March 2022 which is located in the Pecinta Alam Bahari (PAB) area of ​​Dumai City. The method used is an experimental method with plastic cover treatment with different colors. This experiment has one factor, namely plastic color, with four levels of treatment, namely no plastic (control), clear, red, and black colors. The type of plastic used is the same type of plastic. The experimental units are made of iron which is assembled with a size of 1x1m and 12 subunits are measuring 10x10 cm. Observations were made every day for three consecutive days. The results showed that there were 15 species of epipelic diatoms, where the species that were often found every day were Cosdisnodiscus sp., Gyrosigma sp., Navicula sp., and Pleurosigma sp., Skeletonema sp, Striatella sp, Synedra sp. The abundance of diatoms in the treatment without plastic ranged from 38993.8 - 68239.2 ind/cm2, the clear plastic cover ranged from 39880.04 to 67353.0 ind/cm2, the red plastic cover ranged from 31904.0 to 69125.4 ind/cm2, and the black plastic cover ranged from 28359.14 – 54945.83 ind/cm2. The results of the One Way Anova test between treatments showed a significant difference every day, except on day 0 which was not significantly different.